Business Competitiveness Strategies of Tax Consulting Firm amidst Covid-19 Pandemic (Case Study at PT XYZ) - Prianto Budi Saptono; Ismail Khozen (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2021)
This study aims to examine the competitive strategies of companies in facing thechallenges of the Covid-19 pandemic with a case study on a tax consulting firm in Jakarta("PT XYZ"). PT XYZ was selected because, during the pandemic, it employs even moreemployees, with the current number of permanent employees above a hundred. We usequalitative methods in conducting this study with data collection through in-depthinterviews and analysis techniques using SWOT analysis. This study indicates that it isbecoming increasingly critical for organizations to implement a competitiveness plan todeal with the challenges of the coming years. Digital marketing development should beprioritized in competitive plans to ensure survival and ultimate success, especially for PTXYZ and other tax consulting firms in a similar circumstance. This study contributes toestablishing a foundation for organizations to become more resilient by transformingthreats they face into opportunities for growth.